Macro and Micro Factor Influencing Tech Startup Valuation of Private Markets in ASEAN Countries - Chandra Setiawan; Rizki Ramdha Maarif (Australasian Accounting, Business and Finance Journal, 2024)
Startups in ASEAN countries, including Indonesia, Malaysia, Singapore, Thailand, Vietnam, and the Philippines, have grown rapidly over the past five years. However, the current global economic uncertainty has created an imbalance that affects the budding startup ecosystem in ASEAN. A study used econometrics software and secondary data to understand how macroeconomic factors like GDP growth, country risk premium, and initial capital increases affect startup valuations in private markets in these six ASEAN member countries. Seventy-two sample data from deals between 2020 and 2022 were analyzed using various quantitative methods, such as panel data testing, T-test, and F-test. The findings indicate that the amount of money collected and the country's risk premium significantly affect startup valuations in these six member countries. However, GDP growth does not have a statistically significant effect. The F-Test shows that the Average Money Raised, the Country's Risk Premium, and GDP Growth all significantly affect startup valuations in the private markets of these six ASEAN member countries when analyzed simultaneously. The T-test reveals that the Average Money Raised is the most significant independent variable. Therefore, investors should continue fundraising, and the government should create a favorable business environment for startups and themselves. These findings could help stakeholders interested in technological investments to evaluate strategic investment in private markets in Indonesia, Malaysia, Singapore, Thailand, Vietnam, and the Philippines. It could also help academics analyze and understand "Factors Influencing Startups Valuation in Private Markets" and assist other researchers in further developing this study.
Keywords: Country’s Risk Premium; GDP Growth; Money Raised; Private Markets; Startups; Startups Pre-Money Valuation